Ichthyosis follicularis, atrichia, and photophobia syndrome associated with a new mutation in MBTPS2. (1st July 2015) - Fong, K.; Takeichi, T.; Liu, L.; Pramanik, R.; Lee, J.; Akiyama, M.; McGrath, J. A.
Summary: Ichthyosis follicularis, atrichia and photophobia (IFAP) syndrome (OMIM 308205) is a rare X‐linked genetic disorder. Mutations in MBTPS2 underlie IFAP syndrome, with 19 different mutations reported to date. Keratosis follicularis spinulosa decalvans (KFSD) is an allelic disorder that results from a single recurrent mutation, p.Asn508Ser. We report a case from the UK of IFAP syndrome resulting from a new mutation, p.Asn508Thr, emphasizing the significant overlap between IFAP and KFSD at both the molecular and clinical levels. An area of alopecia on the scalp of the proband's mother was also noted, suggesting lyonization.